A Desolvation‐Free Sodium Dual‐Ion Chemistry for High Power Density and Extremely Low Temperature. Issue 44 (21st September 2021) - Chen, Jiawei; Peng, Yu; Yin, Yue; Fang, Zhong; Cao, Yongjie; Wang, Yonggang; Dong, Xiaoli; Xia, Yongyao
Abstract: The development of conventional rechargeable batteries based on intercalation chemistry in the fields of fast charge and low temperature is generally hindered by the sluggish cation‐desolvation process at the electrolyte/electrode interphase. To address this issue, a novel desolvation‐free sodium dual‐ion battery (SDIB) has been proposed by using artificial graphite (AG) as anode and polytriphenylamine (PTPAn) as cathode. Combining the cation solvent co‐intercalation and anion storage chemistry, such a SDIB operated with ether‐based electrolyte can intrinsically eliminate the sluggish desolvation process. Hence, it can exhibit an extremely fast kinetics of 10 Ag −1 (corresponding to 100C‐rate) with a high capacity retention of 45 %. Moreover, the desolvation‐free mechanism endows the battery with 61 % of its room‐temperature capacity at an ultra‐low temperature of −70 °C. This advanced battery system will open a door for designing energy storage devices that require high power density and a wide operational temperature range. Abstract : A desolvation‐free sodium dual‐ion battery was fabricated by combining reversible anion doping in a polytriphenylamine (PTPAn) cathode and co‐intercalation of a Na + ‐solvent complex in an artificial graphite (AG) anode, which demonstrates super‐fast kinetics of 10 Ag −1 (100C‐rate) at 25 °C, maintaining 61 % at an ultra‐low temperature of −70 °C compared to its room‐temperature capacity.